Teach4you - Omar, Bara'a; Jawabreh, Raheeq; Darawsheh, Arwa (My University, 2019)
Student in general suffer from the problem of lack of regular study and follow-up daily themselves on the night of the exam know little about the course and also may not have anything related to summaries or explanation of another course. Hence came the idea of the project teach4you where is an educational site dedicated for students where this site has been designed by a director who is responsible for adding the students' needs. It contains book, summaries, previous examinations, assignments and lectures.